Evaluación del potencial de rendimiento de grano de dos Sorgos Híbridos con fertilización diferenciada en la zona de Babahoyo - Montezuma Peñafiel, Héctor Luis (2014)
This research was carried out in the grounds of the Quinta " Coca Mejía " pertaining to Mr. Mejia Coca Philadelphus, located at km 9 Via Babahoyo - Montalvo, Rivers Province, in sorghum hybrids ' P83G19 ' and ` P84G11 ', tested doses of fertilizers: 95,14 - 40 - 100, 125,14 - 50 - 125; 155,14 - 60 - 150; 185.14 to 70 - 175; 215,14 - 80 - 200 and 0 - 0 - 0 kg / ha of NPK , with : 1 ) evaluate the potential performance of hybrid sorghum , 2) identify the proper nutritional program to maximize grain yield , 3) determine the agronomic efficiency of hybrids , and 4) Analyze the economic grain yield depending on the production cost of the treatments and sub-treatments. Experimental design "split plots" was used in three replications. The main plots corresponded to hybrids (treatments) and levels of chemical fertilization (subtratamientos) as experimental subplots. The experimental subplot consists of 4 rows of 6 m length spaced at 0.50 m, giving an area of 2.0 m x 5.0 m = 10.0 m2, the useful area of the experimental subplot was 5.0 m, determined by the two central rows...........